Correlation-bound anions of NaCl clusters - Sommerfeld, Thomas; Bhattarai, Bijay; Vysotskiy, Victor P.; Cederbaum, Lorenz S. (The journal of chemical physics, 2010)
In the past a variety of electron binding motifs has been identified for sodium chloride cluster anions. As for all of these clusters the excess electron is predicted to be bound in self-consistent-field calculations, the different binding mechanisms can be understood in terms of a one-electron potential largely due to the permanent multipole moments of the neutral cluster. Here we investigate a new class of (NaCl)N− anion that is predicted to be bound only after electron correlation has been taken into account. Correlation-bound states of the trimer, (NaCl)3−, and tetramer, (NaCl)4−, are characterized using Green’s function and an equation-of-motion coupled-cluster method, and the computed electron binding energies as well as the distributions of the excess electrons as inferred from natural orbitals of the coupled-cluster calculations are compared with that of dipole-bound, quadrupole-bound, and defectlike (NaCl)N− anions. For the (NaCl)4− tetramer anion the correlation-bound state is predicted to represent the most stable isomer. Our results provide a sensitive test case for the development of improved one-electron model potentials for excess electrons bound to alkali halide clusters, and suggest that cluster abundance as inferred from peak intensities of photoelectron spectra is not directly related to the relative stability of the clusters.
Gesehen am 14.09.2023